Quality of Service (QoS) for Network Performance Analysis Wireless Area Network (WLAN) - Muhammad Yasin Simargolang; Adi Widarma (Universitas Negeri Medan, 2022)
Quality of Service (QoS) is the ability of a network to provide good service by providing bandwidth, overcoming jitter and delay. Wireless LAN network performance must always be maintained properly. Therefore, to determine the quality of the wireless LAN internet network at Asahan University, it is necessary to analyze network performance, focus on how to monitor and measure the performance of the wireless LAN network, and find out how big the network performance is on the infrastructure. as the speed of access from the sending point to the destination point. Access speed is measured by measuring throughput, delay, jitter and packet loss on the network at Asahan University. Research conducted using quantitative methods consists of 4 stages, namely conceptual, design, empirical and analytical. In the QoS (Quality of Service) analysis carried out using the Wireshark application and using the TIPHON standard, the results obtained from the quality of the WLAN network of each faculty at Asahan University are different. Throughput measurement obtained an average result of 582.08 Kb/s and is categorized as medium. The average packet loss measurement result is 5.39% and is categorized as good. The delay measurement results obtained an average of 15.62 ms and is categorized as very good. The average result of the jitter measurement is 4.50ms with good category.